2012
DOI: 10.1186/1753-2000-6-34
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum symptoms in children with neurological disorders

Abstract: BackgroundThe aims of the present study were to assess symptoms associated with an autism spectrum disorder (ASD) in children with neurological disorders as reported by parents and teachers on the Autism Spectrum Screening Questionnaire (ASSQ), as well as the level of agreement between informants for each child.MethodsThe ASSQ was completed by parents and teachers of the 5781 children (11–13 years) who participated in the second wave of the Bergen Child Study (BCS), an on-going longitudinal population-based st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…Detailed analysis of response patterns indicates that parents tend to endorse more polar ratings (i.e. present or absent) while teachers tend to rate skills as developing or use more moderate categories (Ryland et al 2012; Voelker et al 2000). These differences in response patterns may be strongly influenced by the contextual variation between informants (De Los Reyes et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analysis of response patterns indicates that parents tend to endorse more polar ratings (i.e. present or absent) while teachers tend to rate skills as developing or use more moderate categories (Ryland et al 2012; Voelker et al 2000). These differences in response patterns may be strongly influenced by the contextual variation between informants (De Los Reyes et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Such disabilities are strongly associated with mental health problems irrespective of being born premature. [16][17][18][19] Assessment of mental health in children with severe NDDs, such as intellectual disability (ID) (IQ <70), requires appropriately validated tools, 18,20,21 but most EP/ELBW studies have included children with severe NDDs without using instruments validated for this subgroup. [1][2][3][4][5][6][7][8][9][10][11][12][22][23][24] In subanalyses, some studies have found increased risk of mental health problems in EP/ELBW children without severe NDDs, but frequencies and effect sizes were not reported.…”
mentioning
confidence: 99%
“…This is consistent with the findings of previous studies in the area. 30 31 However, the feasibility of collecting questionnaires from child participants was questionable due to low response rates and parent reports of low validity. Two outcome measures, the SRS-2 22 and the custom-made goal-based measure, showed high levels of completion rates (for teachers), good face validity and a trend in the desired direction indicating that they would be suitable for use as primary outcome measures in a full scale trial.…”
Section: Discussionmentioning
confidence: 99%